Effect of Mordant Types on the Characteristics of Eco-Printed Leather using Bark-Based Natural Dyes for Veterinary Health Applications - Putri, Naimah; Rahmawati, Atiqa; Wibowo, Raden Lukas Martindro Satrio Ari (Faculty of Animal Science Universitas Brawijaya, 2026)
This study aimed to evaluate the characteristics of eco-printed leather dyed with natural dyes and treated with various mordants before the dyeing process. Dye penetration from Sappanwood, Tegeran, and Jalawe dyes was assessed at intervals of 30 min, 60 min, and 90 min. In the eco-printing part of the study, samples treated with three different mordants were compared: Mordant A (Al?(SO?)?), Mordant B (CaCO?), and Mordant C (FeSO?). The quality of eco-printed leather was evaluated by measuring parameters such as tensile strength, elongation, tear strength, thickness, and color fastness to rubbing. The results showed that the optimal dye penetration time for all natural dyes on leather was 60 min. Physical quality tests revealed that leather treated with CaCO? and dyed with Sappanwood had the highest elongation (59.998 ± 15.96%) and tensile strength (15.323 ± 0.885 N/cm²). Conversely, Tegeran dye combined with Al?(SO?)? produced the strongest tear strength (21.475±0.206 N/mm). Regarding rubbing fastness, all mordants performed similarly, scoring from 3 (sufficient) to 4 (good). For dry rubbing, all mordants scored between 3 (good) and 4 (good). However, in wet rubbing tests, FeSO? was rated lower, with scores ranging from 1 to 2 (poor).